What explains immigrant-native gaps in European labor markets: the role of institutions - Guzi, Martin; Kahanec, Martin; Mytna Kurokeva, Lucia (Bonn, 2015)
"The role of institutions in immigrant integration remains underexplored in spite of its essential significance for integration policies. This paper adopts the Varieties of Capitalism framework to study the institutional determinants of Immigrant-Native gaps in host labor markets. Using the EU LFS we first measure immigrant-native gaps in labor force participation, unemployment, low-skilled employment and temporary employment. We distinguish the gaps that can be explained by immigrant-native differences in characteristics from those that cannot be explained by such differences, as these require different integration policy approaches. In the second stage we measure the effects of institutional and contextual variables on explained and unexplained immigrant-native gaps. Our findings confirm that institutional contexts play a significant role in immigrant integration, and highlight the importance of tailoring policy approaches with regard to the causes of immigrant-native gaps."